Blinded comparison of cranial CT and MR in closed head injury evaluation. - Orrison, W W; Gentry, L R; Stimac, G K; Tarrel, R M; Espinosa, M C; Cobb, L C (American Journal of Neuroradiology, 1994)
PURPOSE To compare CT and MR in the evaluation of acute head injury. METHODS One hundred seven consecutive patients who were referred to the emergency department and underwent both MR and CT cranial examinations within 48 hours were retrospectively reviewed. The films were interpreted by two neuroradiologists blinded to all patient information. RESULTS The sensitivity of MR was significantly higher than that of CT for the detection of contusion, shearing injury, subdural and epidural hematoma, and sinus involvement. The sensitivity of CT was significantly higher than that of MR for the evaluation of fracture. The sensitivities of MR and CT were statistically equivalent for the detection of superficial soft-tissue injury. The overall sensitivity of MR for the detection of abnormalities in acute head trauma was 96.4%, and for CT was 63.4%. CONCLUSIONS CT and MR are complementary studies in the evaluation of acute head trauma. MR is necessary to define or exclude contusions, deep shearing injury, and extraaxial fluid collections in acute head trauma.